Raising Taxpayer Awareness Through e-Filing Education by Tax Volunteers at KPP Pratama Semarang Gayamsari - Irma Istiariani; Muhammad Salman Alfarisy; Defy Rizka Amailiya; Dian Novita Setiyaningrum; Ferliana Nava Pratiwi; Muhammad Fikri Priyadi; Syibhul Ashfia (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Reporting Annual Tax Returns is now easier with e-filing. The existence of e-filing means that taxpayers can report their annual SPT anywhere and anytime. However, the reality in the field is that many taxpayers do not understand the use of e-filing. One of these obstacles is a lack of education on the use of e-filing. The Directorate General of Taxes, as the authority in regulating tax administration, has created a service program through assistance with Annual SPT Reporting. The program is called RENJANI or commonly called Tax Volunteers for the Country whose task is to provide community service, especially taxpayers, in the form of outreach and education about taxation. This program was attended by many students who collaborated with Tax Center institutions from various universities in Indonesia. The method of implementing community service carried out by tax volunteers is to assist in reporting the Annual Tax Returns of individual taxpayers and employees and provide education about obligations in tax matters. This program has helped as many as 492 taxpayers in reporting their Annual SPT. With this program, it is hoped that it will be able to increase taxpayer awareness and increase taxpayer compliance in Indonesia.